Answer:
f = e/2
Step-by-step explanation:
e = 2f
Switch sides.
2f = e
Divide both sides by 2.
f = e/2
Simplify
Let's simplify step-by-step.
x(5)−3(x−4)
Distribute:
=x(5)+(−3)(x)+(−3)(−4)
=5x+−3x+12
Combine Like Terms:
=5x+−3x+12
=(5x+−3x)+(12)
=2x+12
Answer:
=2x+12
Answer:
you need to show more for help
Step-by-step explanation:
Answer:
The answer is A. Substitution
Step-by-step explanation:
Looking at the previous proofs, you can see that:
∠Y≅∠4
∠Z≅∠6
∠X + ∠4 + ∠6 = 180°
Statement 5 then replaces ∠4 and ∠6 with ∠Y and ∠Z, respectively. Replacing it means that it was substituted with the GIVEN values by the previous statements.
The best answer is the Substitution.
0.0006 would be your answer based on the order you put them in.